The Effects of Backpack Weight on the Static and Dynamic Balances of Female Students - Saeid Bahiraei; Maryam Jafarian; Ebrahim Mohammad Ali Nasab (The Society of Aging and Physical Activity (SAPA), 2015)
The main aim of this study was to investigate the effects of carrying backpack on the balance of female students aged 9-11 years. In the present study, 30 students (mean age of 15.02±2.07 years, height of 140±8 cm, and weight of 41.51±15.26 kg and body mass index of 20.68±5.39 kg/m2) were randomly selected. Their static and dynamic balances were evaluated using single-leg stance and Y tests in both cases of with and without a backpack. Based on the research findings, there was a significant difference (P═0.035) between the cases of with and without carrying a backpack (as much as 10% of body weight) in a static balance in girls aged 9-11 years. Also, a significant difference was found between the anterior direction (P═0.003) in the left leg and internal posterior (P═0.003) and external posterior (P═0.003) directions in the right leg in the dynamic balance, while no significant differences were seen in other directions in the two legs. Moreover, in the assessment of the effect of backpack on different directions using Y test, it was observed that backpack weight has the greatest effects on both legs in the internal posterior direction. The results of the current research showed that carrying a backpack weighing 10% of the body weight by female students aged 9-11 reduced static and dynamic balances. According to the results, it is suggested that school health officials and parents should apply effective planning and training for students on carrying backpack with suitable weight.